Guillaume : A Life - Guillaume, Robert (Book collections on Project MUSE., 2002)
"Guillaume: A Life is the autobiography of esteemed Broadway, Hollywood, and television star Robert Guillaume. Ten months after suffering a stroke, Guillaume - perhaps best known as television's Benson - began this autobiography with author and collaborator David Ritz." "The book goes beyond the recounting of a long and successful career to examine the forces that shaped the man: family, religion, race, and class. Startlingly candid and disarmingly self-aware, Guillaume seeks to know and understand himself, his treatment of the women in his life, and the choices he made along the way. He pursues the truth, however painful it may be, says Ritz, guided by two questions, "Who the hell am I?" and "What made me do what I did?""--Jacket.